Challenges in postgraduate medical education during the COVID-19 pandemic - Aldo Medina-Gamero; Emilio Rosario-Pacahuala (Revista de la Facultad de Medicina)
Postgraduate medical education faced several challenges during the COVID-19 pandemic due to the need to implement an online education system. For example, training teaching staff in the use of e-learning tools and platforms or including sufficient content on such platforms to ensure that students learn appropriately. While these problems were successfully addressed during the pandemic in Peru, we believe that there are other difficulties that also need to be addressed.